Genetic polymorphisms-137 (G > C) (rs187238) and-607 (C > A) (rs1946518) and serum level of interleukin 18 in Fars ethnic groups with metabolic syndrome in Northern Iran - Aghajani, Roja; Saeidi, Mohsen; Amiriani, Taghi; Marjani, Majid; Amiriani, Amir Hossein; Tabib, Atefeh Akhavan; Marjani, Abdoljalal (Taylor & Francis Ltd, 2022)
Introduction:We aimed to determine the genetic polymorphisms and serum level of interleukin 18 in Fars ethnic groups. Material and methods:226 Fars ethnic groups were participated. The ATP III criteria were used to assess MS components. The SNPs of the IL-18 gene were determined with ARMS-PCR. Results:The GG, GC, and CC genotypes of -137 were 50%, 40%, and 10%. The CC, CA, and AA genotypes of -607 were 45%, 37%, and 18%. The GG, GC, and CC genotypes of -137 were 44.20%, 43.40%, and 12.40%, and were 55.75%, 36.28%, and 7.97% in subjects with and without MS, respectively. The CC, CA, and AA genotypes of -607 were 48.70%, 37.20%, and 14.20% and were 41.60%, 37.20%, and 21.20% in both groups, respectively. Conclusion:IL-18 gene may different in specific populations, different ethnic groups and geographic regions. The IL-18 polymorphisms might not be used as a marker of metabolic syndrome.
Keywords: Genetic polymorphism; interleukin 18; Fars ethnic; metabolic syndrome; Iran